(untitled) (Trabalho & Educação, 2016)
In Brazil the first records of distance education date back to the early twentieth century. Since then, there were many projects and laws that were processed in the Senate in order to better structure the activity of teaching. However, an important point in this process is still clarify the role of the tutor. This is not a very simple task, because of the complexity of their role, changes in the historical cultural setting and advances of information and communication technologies. The impact of these changes in education can be perceived in many ways, since the number of information accessible to all till the social exclusion of regions and disadvantaged individuals. It caused by long geographic and social distances. With this regard, in 2006, the Brazilian government has strengthened the proposal for access to higher education and social development through distance education. In order this, he sanctioned laws and promoted access to the Brazilian population. With this process the figure of the tutor is embodied in the... ___ No Brasil os primeiros registros de educação a distância remontam o início do século XX. De lá para cá foram muitos os projetos e leis que tramitaram no Senado com o intuito de melhor estruturar essa atividade de ensino. No entanto, um dos pontos importantes nesse processo ainda é clarear o papel do tutor. Isto não é uma tarefa muito simples, dada a complexidade do seu papel, as mudanças no cenário histórico cultural e os avanços das tecnologias da informação e comunicação. O impacto dessas mudanças na educação pode ser percebido de muitas maneiras, do número de informações acessíveis e abertas a todos até a exclusão social, de regiões e indivíduos desfavorecidos, provocada por longas distâncias geográficas e sociais. Com esse olhar, em 2006, o governo Brasileiro fortaleceu a proposta de acesso a uma formação superior e desenvolvimento social a partir da educação a distância, sancionando leis e fomentando o acesso de toda a população brasileira. Com esse processo a figura do tutor toma corpo no...